2015
DOI: 10.1039/c5nr02328a
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the size effect of room temperature nanoimprinted P3HT nanopillar arrays on the photovoltaic performance

Abstract: We develop a solvent-assisted room temperature nanoimprint lithography (SART-NIL) technique to fabricate an ideal active layer consisting of poly(3-hexylthiophene) nanopillar arrays surrounded by [6,6]-phenyl-C61-butyric acid methyl ester. Characterization by scanning electron microscopy, two-dimensional grazing incidence wide angle X-rays diffraction, and conducting atomic force microscopy reveals that the SART-NIL technique can precisely control the size of P3HT nanopillar arrays. With the decrease in diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Typically, cSFM requires contact mode operation. However, the contact mode operation on soft samples can lead to surface deformation, such that fragile polymer nanopillar structures can be easily bent or even destroyed . To reduce or minimize this deleterious effect, a new cSFM mode has recently been developed, which is based on the torsion mode and/or on the peak force.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Typically, cSFM requires contact mode operation. However, the contact mode operation on soft samples can lead to surface deformation, such that fragile polymer nanopillar structures can be easily bent or even destroyed . To reduce or minimize this deleterious effect, a new cSFM mode has recently been developed, which is based on the torsion mode and/or on the peak force.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular orientation as well as domain size could be tailored with different kinds of templates and surface treatments. Silicon molds and anodized aluminum oxide (AAO) templates have typically been employed to realize nanopillars with diameters ranging from 20 to 250 nm. Several studies have shown that the power conversion efficiency increases when the donor–acceptor distance approaches the exciton diffusion length .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ordered heterojunction solar cell devices fabricated with the P3HT nanorod arrays had a PCE ≈2.4% . As the diameter of the P3HT nanorods is decreased, the proportion of P3HT chains in the face‐on orientation with respect to the substrate plane increases and the conductivity along the axis of the nanorods increases . These ordered heterojunction devices have lower energetic disorder and a lower density of trap states than conventional BHJ or planar heterojunction devices, and therefore exhibit less charge recombination loss .…”
Section: Morphology Controlmentioning
confidence: 99%